The Effect of Implementing Patient Safety on the Quality Service in the Inpatient Room of General Hospital, Indonesia - Nadapdap, Marshall Jeremia; Fitriani, Arifah Devi (Jurnal Perilaku Kesehatan Terpadu, 2023)
Quality service quality with a guarantee of high patient safety produces a good hospital image in the eyes of patients as hospital consumers. The aim of the research was to determine the effect of implementing patient safety on the quality of service in the Inpatient Room at Kindergarten Hospital. II Putri Hijau Medan.Analytical survey research design with a cross sectional approach. The population of all inpatients was 270 people and the accidental sampling sample was 73 people. Primary data collection methods, secondary and tertiary data. The data analysis used is the binary logistic regression test.The results of the study showed that identifying patients had a sig-p value of 0.004 < 0.05, communication sig-p 1,000 > 0.05, drug safety sig-p 0.029 < 0.05, risk of wrong location, wrong patient and surgery sig-p 0.598 > 0.05, risk of infection sig-p 0.010 < 0.05 and risk of patient falls sig-p 0.025 < 0.05.The conclusion in this study is that there is an influence of patient identification, drug safety, risk of infection and risk of patient falls on the quality of service, while communication and the risk of wrong location, wrong patient and surgery have no influence on the quality of service. It is hoped that the results of this research can become a reference for the Tk Hospital. II Putri Hijau Medan to better understand the importance of patient safety management in accordance with Ministry of Health regulations in order to maximize the quality of health services achieved.